Mobile tracking system on android using global positioning system / Nik Mohd Faris Nik Kamarudin - Nik Kamarudin, Nik Mohd Faris (2013)
The mobile tracking system provides the capability of tracing people using Global Positioning System (GPS). In mobile tracking system, the users’ coordinates will be sent to the mobile by the GPS satellite. However, not many people used the GPS to search their friends. Many of them used the GPS only to search places. So, the mobile tracking system is not frilly utilized. In order to overcome this problem, some solution has been discovered. It is the mobile tracking system that is implemented on android phone focusing on searchig people. By using this system, it will store the location of the people that registered through the system and can retrieve it back. The coordinates will be plotted on the Google Maps that is connected to the Google Maps server. The development of M-TrackSys are based on the research methodoloy such as preliminary study, system analysis, system design, system development, system testing and evaluation and documentation. Based on premilinary study, M-TrackSys is designed by using 3-Tier architecture which consists of presentation or GUI tier, application tier and database tier. The mobile tracking system (M-TrackSys) has been tested in UiTM Dungun Terengganu. The result of this proposed system is evaluated based on the user interface, usability and functionality by set of questionnaire. The result have shown that the overall gave 70% positive feedback about the M-TrackSys.